Role of IgM antibodies versus B cells in influenza virus-specific immunity. - Kopf, M; Brombacher, F; Bachmann, M (2002)
We have compared the role of IgM antibodies with the role of B cells in control of primary influenza virus infection. Mice deficient in IgM (IgM(-/-)), but capable of producing other Igisotypes, exhibited increased pulmonary virus titers compared to wild-type mice. However, IgM(-/-) mice were less susceptible compared to B cell-deficient micro MT) mice. CD4(+) T cells from spleen and lung draining lymph nodes of infected micro MT mice showed reduced proliferation upon virus re-stimulation in vitro. Furthermore, numbers of IFN-gamma-producing CD4(+) effector T cells were reduced in the alveolar lavage (BAL) of micro MT mice but not IgM(-/-) mice. In contrast, total number of virus-specific CTL was almost comparable in BAL of micro MT and wild-type mice. Pulmonary recruitment of inflammatory macrophages and neutrophils occurred normally in both micro MT and IgM(-/-) mice. Interestingly, virus-specific IgG2a and IgG2b antibody responses were affected locally in the BAL and in the serum of IgM(-/-) mice, while IgG1 responses remained largely normal. Taken together, our data suggest a role for B cells to promote effector T cell responses and a role of both IgM and IgG antibodies in the defense against acute influenza virus infection.